Ionic liquid and magnesium hydrate incorporated conjugated microporous polymers nanotubes with superior flame retardancy and thermal insulation. (24th April 2020) - Zhu, Zhaoqi; Wu, Shujuan; Liu, Chao; Mu, Peng; Su, Yanning; Sun, Hanxue; Liang, Weidong; Li, An
Abstract: The development of efficient thermal insulation materials with better flame-retardant property is of great importance for thermal energy saving in many aspects. Herein, we report the preparation of monolithic conjugated microporous polymers nanotubes (M-CMPsN) by Pd (0)/Cu I catalytic Sonogashira - Hagihara cross-coupling reaction using 1, 3, 5-triethynylbenzene and 2, 4, 6-tribromoaniline as building blocks. The M-CMPsN samples exhibit excellent mechanical property with a compressive strength of 92 kPa at 70% stain. Taking advantage of their abundant porosity, the M-CMPsN samples show superior thermal insulation with a low thermal conductivity of 0.03 W m −1 k −1 in air. The N-rich feature of the M-CMPsN also endows them better flame retardancy. To further enhance their flame retardant property, the incorporation of Mg(OH)2 and ionic liquid into M-CMPsN was performed and the results show that flame retardancy of the treated M-CMPsN samples could be significantly improved, e.g. its peak heat release rate (pHRR) value is only one fifth of that of the untreated M-CMPsN, making them promising candidates as thermal insulation and flame retardant coating materials with great potentials for thermal energy saving applications. Graphical abstract: Image 10382 Highlights: The M-CMPsN exhibits excellent mechanical property and superior thermal insulation. The N-rich feature of the M-CMPsN endows them better flame retardancy. The M-CMPsN can be used as a thermal insulation and flame-retardant coating material.